ThinSight: integrated optical multi-touch sensing through thin form-factor displays - Izadi, Shahram; Hodges, Steve; Butler, Alex; Rrustemi, Alban; Buxton, Bill (EDT '07: Proceedings of the 2007 workshop on Emerging displays technologies, 2007)
ThinSight is a novel optical sensing system, fully integrated into a thin form factor display, capable of detecting multiple objects such as fingertips placed on or near the display surface. We describe this new hardware, and demonstrate how it can be embedded behind a regular LCD, allowing sensing without compromising display quality. Our aim is to capture rich sensor data through the display, which can be processed using computer vision techniques to enable interaction via multi-touch and physical objects. A major advantage of ThinSight over existing camera and projector based optical systems is its compact, low profile form factor making such interaction techniques more practical and deployable in real-world settings.